Comparison of Renal Safety of Tenofovir and Telbivudine in Chronic Hepatitis B Patients: A Real World Study in Indonesia - Rino Alvani Gani (Jurnal Penyakit Dalam Indonesia)
Introduction. Tenofovir disoproxil fumarate (tenofovir) and telbivudine are two available nucleos(t)ide analogue (NA) for the treatment of chronic hepatitis B (CHB) patients. Tenofovir has been known as a nephrotoxic agent in HIV patients, but still controversy in CHB patients. On the other hand, telbivudine had a renal protective effect and increased estimated glomerular filtration rate (eGFR). This studi aimed to address the renal safety of tenofovir and telbivudine in Indonesian patients.